Examining the Role of Employee Mental Well-Being in Enhancing Work Engagement and Task Performance among Health Employees in the Public Sector: The Case of Chibombo District - Lungowe Chindele; Chilayi Mayondi; Victor Chikampa; Jacqueline Siwale; Angelo Salasini; Chimuka Mwaanga (International Journal of Humanity and Social Sciences, 2026)
Purpose: The study examined the role of employee mental well-being in enhancing work engagement and task performance among public sector healthcare workers in Zambia. Drawing on the Job Demands–Resources (JD-R) Theory, the study proposed that employee mental well-being promotes work engagement, which subsequently enhances task performance. It further assessed whether mental well-being and work engagement significantly predict employee task performance. Methodology: A quantitative cross-sectional survey design was employed using a sample of 120 healthcare workers from Chibombo District selected through simple random sampling. Data were collected using the Warwick–Edinburgh Mental Well-being Scale, the Utrecht Work Engagement Scale (UWES-9), and the Individual Work Performance Scale. The instruments demonstrated satisfactory reliability (α = .92, .90, and .88, respectively). Data was analyzed using SPSS Version 27 through descriptive statistics, Pearson correlation, and multiple regression analyses. Findings: The findings revealed significant positive relationships between employee mental well-being and work engagement (r = .893, p < .01), mental well-being and task performance (r = .842, p < .01), and work engagement and task performance (r = .882, p < .01). Regression analysis further showed that employee mental well-being (β = .270, p < .05) and work engagement (β = .641, p < .001) significantly predicted task performance, jointly explaining 79.2% of its variance (R² = .792). Work engagement emerged as the strongest predictor of employee task performance. Unique Contribution to Theory, Policy and Practice: The study extends the application of the Job Demands–Resources (JD-R) Theory within the Zambian public healthcare context by demonstrating that employee mental well-being is a key psychological resource that enhances work engagement and task performance. The findings provide empirical evidence to inform organizational policies aimed at strengthening employee well-being, psychosocial support, and work engagement programmes to improve employee productivity, service delivery, and organizational effectiveness in Zambia's public health sector.